2018
DOI: 10.1007/s10567-018-0261-x
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Adolescent Peer Relations in the Social Media Context: Part 1—A Theoretical Framework and Application to Dyadic Peer Relationships

Abstract: Investigators have long recognized that adolescents' peer experiences provide a crucial context for the acquisition of developmental competencies, as well as potential risks for a range of adjustment difficulties. However, recent years have seen an exponential increase in adolescents' adoption of social media tools, fundamentally reshaping the landscape of adolescent peer interactions. Although research has begun to examine social media use among adolescents, researchers have lacked a unifying framework for un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
531
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 399 publications
(546 citation statements)
references
References 170 publications
(282 reference statements)
13
531
0
2
Order By: Relevance
“…Important developmental tasks of adolescence include the establishment of intimate peer relationships, increasing independence from adults, and the exploration of identity [9]. Social media offers a prime context for navigating these tasks in new, increasingly complex ways: peers are constantly available, personal information is displayed publicly and permanently, and quantifiable peer feedback is instantaneously provided in the form of "likes" and "views" [10].…”
Section: Adolescence and The Media Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…Important developmental tasks of adolescence include the establishment of intimate peer relationships, increasing independence from adults, and the exploration of identity [9]. Social media offers a prime context for navigating these tasks in new, increasingly complex ways: peers are constantly available, personal information is displayed publicly and permanently, and quantifiable peer feedback is instantaneously provided in the form of "likes" and "views" [10].…”
Section: Adolescence and The Media Landscapementioning
confidence: 99%
“…Adolescents' peer experiences play a critical role in the onset and maintenance of psychopathology. Within the social media environment, peer interactions can occur with increased frequency, immediacy, and intensity [10]. Specific online peer experiences have been identified in prior work as potential risk factors for mental health concerns.…”
Section: Potential Risks Of Social Media For Adolescent Mental Healthmentioning
confidence: 99%
“…Psychosocial factors also may change the potential effects of digital media use on psychological adjustment. For instance, our own work suggested that among low social status teens, but not among those with average or high levels of status, online social comparison (or status seeking) creates unique vulnerabilities for low self‐image, social distress, and perhaps even online harassment (see Nesi et al, ). Unfortunately, too few studies offer a thorough examination of how demographic or psychological risk factors may transact with the affordances of digital environments to create both adaptive and maladaptive social experiences online.…”
mentioning
confidence: 99%
“…Social media plays a role in adolescent social life and explaining how social media use can possibly influence something as complex as mental health requires a holistic theoretical framework. The transformation framework (Nesi et al, 2018a(Nesi et al, , 2018b proposes that the unique context of social media fundamentally transforms adolescents' peer experiences across multiple domains. For example, through what is referred to as asynchronicity or the time that passes between responses in a dialogue online, adolescents can carefully select their words and engage in many conversations at the same time, as well as decide how to present themselves.…”
mentioning
confidence: 99%